BEYOND DIRECTIONS: HOW TOUR GUIDES SHAPE CULTURAL INTERPRETATION AND VISITOR ENGAGEMENT AT CULINARY FESTIVALS - Debi Rusmiati; Ahmad Kurniawan (Politeknik Pariwisata Palembang, 2025)
Culinary festivals have increasingly emerged as important platforms for cultural tourism, offering visitors opportunities to engage with local heritage through food-based experiences. However, limited attention has been given to the role of tour guides in shaping cultural interpretation and visitor engagement within culinary festival settings. This study aims to examine how tour guides influence visitors’ cultural understanding and engagement at the Festival Kuliner Legendaris Jakarta. Adopting a qualitative case study approach, data were collected through in-depth semi-structured interviews, participant observation, and document analysis involving tour guides, festival visitors, and event organizers. The data were analyzed using thematic analysis to identify patterns related to guiding practices and visitor experiences. The findings reveal that tour guides play a significant role as cultural interpreters, storytellers, and experience curators by contextualizing local culinary heritage through interpretive narratives and interactive communication. These practices enhance visitors’ cultural appreciation, emotional connection, and overall engagement with the festival experience. This study contributes to tourism and event management literature by extending the understanding of tour guides’ roles in culinary festival contexts and provides practical insights for festival organizers and destination managers in designing culturally meaningful and engaging culinary tourism experiences.